2012
DOI: 10.1097/iae.0b013e31824dae04
|View full text |Cite
|
Sign up to set email alerts
|

Association of Glutathione S-Transferase Pi Isoform Single-Nucleotide Polymorphisms With Exudative Age-Related Macular Degeneration in a Chinese Population

Abstract: Our data suggest that the GSTP1 variant rs1695 moderately increases the risk of exudative AMD. The variant rs1138272 was rare and was not associated with exudative AMD in this Chinese cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, the progression of this disease is determined in 50-60% of cases by the polymorphisms in three genes that encode the following: CFH (rs1061170), ARMS2 (rs10490924), and Il-8 (rs2227306) [93]. Other polymorphisms are less likely to correlate with the development of AMD, but their influence has been confirmed in other studies [81,[93][94][95][96][97][98][99][100][101][102][103][104]. Genes and their polymorphisms are presented in Table 3.…”
Section: The Role Of Polymorphisms In Amdmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the progression of this disease is determined in 50-60% of cases by the polymorphisms in three genes that encode the following: CFH (rs1061170), ARMS2 (rs10490924), and Il-8 (rs2227306) [93]. Other polymorphisms are less likely to correlate with the development of AMD, but their influence has been confirmed in other studies [81,[93][94][95][96][97][98][99][100][101][102][103][104]. Genes and their polymorphisms are presented in Table 3.…”
Section: The Role Of Polymorphisms In Amdmentioning
confidence: 96%
“…In 2012, a Chinese research team analyzed the role of polymorphisms in the GSTP1 gene (rs1695 and rs1138272) in the development of wet AMD stage. The results showed that only rs1695 moderately increases the risk of developing this disease [104]. In the same year, a GST polymorphism study was conducted in Iran [100].…”
Section: Gpx1 Pro197leumentioning
confidence: 99%
“…In 2012, Chinese patients were conducted on the occurrence of variant rs1695 of GSTP1 . The results demonstrated that this allele is correlated with the development of wet AMD [ 223 ]. In the same year, GST polymorphism study was conducted in Iran.…”
Section: The Influence Of Genetic Factors On the Development Of Amdmentioning
confidence: 99%